2008
DOI: 10.1176/ps.2008.59.10.1175
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic Medications for Patients With Bipolar Disorder in the United States: Polytherapy and Adherence

Abstract: Polytherapy was used by one-third of patients initially and at one year, antidepressant use was highly prevalent initially and later, but lack of treatment was prevalent at one year. Plausible clinical and treatment factors were associated with sustained mood stabilizer adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(59 citation statements)
references
References 29 publications
3
51
0
5
Order By: Relevance
“…Existem dados bem heterogêneos quanto à prevalência de síndrome metabólica (SM) em pacientes com TAB, variando de 16,7 a 67% [27][28][29] . Podemos estratificar essa prevalência de acordo com o modelo de tratamento: 36,3% para APS + EH, 36% para APS e 10,5% para EH 30 . Além de complicações clínicas, a SM também é um fator de pior prognóstico para o TAB, apresentando pior funcionamento global e maior prejuízo da função executiva 27 .…”
Section: Transtorno Bipolarunclassified
See 1 more Smart Citation
“…Existem dados bem heterogêneos quanto à prevalência de síndrome metabólica (SM) em pacientes com TAB, variando de 16,7 a 67% [27][28][29] . Podemos estratificar essa prevalência de acordo com o modelo de tratamento: 36,3% para APS + EH, 36% para APS e 10,5% para EH 30 . Além de complicações clínicas, a SM também é um fator de pior prognóstico para o TAB, apresentando pior funcionamento global e maior prejuízo da função executiva 27 .…”
Section: Transtorno Bipolarunclassified
“…Os componentes depressivos do TAB muitas vezes são de difícil tratamento, necessitando, na maioria das vezes, de múltiplas medicações 30,31 . Mesmo com múltiplas medicações, os sintomas residuais dos componentes depressivos são a queixa mais comum em consultas de acompanhamento em pacientes com TAB 31,32 .…”
Section: Transtorno Bipolarunclassified
“…The effectiveness of antipsychotic medications and drug combinations in LTM studies has not been established yet has become one of the main strategies for clinicians. 1,5,6 This strategy may be inferred from the rapid rise in atypical antipsychotic medication sales and increased use of polypharmacy. [7][8][9][10] It is estimated that nearly half of all BD patients who undergo pharmacological therapy still experience a relapse, accentuating the paucity of effective treatments for this highly diverse, complex illness.…”
Section: Sinopsismentioning
confidence: 99%
“…Nevertheless, currently the delay from an initial depressive episode to correct diagnosis and appropriate treatment of bipolar disorder averages 8-10 years internationally, and is even longer when bipolar disorder begins in adolescence (11-12 year delay) or at preadolescent ages (12-16 years) (8,18). Such delays commonly involve overuse of antidepressants, based on incorrect diagnosis of unipolar depression (19,20). More dangerously, delay of correct diagnosis can be fatal in that fully half of long-term suicidal acts among persons eventually diagnosed with bipolar disorder occur within the first 2-4 years of the illness (21).…”
mentioning
confidence: 99%
“…The value of antidepressant treatment for bipolar depression, despite its highly prevalent empirical use, remains controversial (4,19,20,34,35). Some controlled trials found no benefit when an antidepressant was added to a standard mood-stabilizing regimen, or given as a monotherapy in acute bipolar depression (37,38).…”
mentioning
confidence: 99%